Malaysian Domestic Firms' Contribution Towards Community Based Csr - Mansor, Fazreena (2012)
This study examines the level of community based CSR disclosure among Malaysian domestic firms. Content analysis technique was used for this purpose, by way of using simple index scoring to measure the CSR index according to the sub-themes in the community engagement dimension. Studies on CSR disclosure particularly that linked CSR with community involvement is still lacking in developing countries especially Malaysia. Not much research has been to date to examine specifically the extent to which Malaysian domestic firms carry out their CSR activities in order to elevate the living conditions of the community. Hypotheses are testing using regression analysis on 65 domestic firms listed on Main Board of Bursa Malaysia across a representative cross-sectional of the industrial sectors.